Identity and Symbols of Ancient Artistic Sculptures in Kurdistan Region (Raparin Journal of Humanities (RJH), 2025)
This research studies specific areas to discuss the identity of ancient sculpture and its artistic significance and Symbols in the Kurdistan region. The term "Stone Bar" refers to both two-dimensional and three-dimensional engravings on the face of rocks and mountains, achieved by taking small and suitable pieces of rocks and carving them to create sculptures with distinct artistic identities and meanings. Generally, the region between the Tigris and Euphrates rivers (Mesopotamia), namely the Kurdistan region and its surrounding areas, has inherited numerous rock carving artifacts. In addition to rocks, in some other civilizations, wooden carving artifacts have been left in this area due to the ease of obtaining wood from trees and transforming it into household tools and artistic materials at that time. Sculpture, on the other hand, refers to any statue created through construction or the addition of parts made from various raw materials, aimed at expressing different artistic themes and projects.This research represents an intellectual and aesthetic exploration of expressions and the discovery of identity and artistic meanings in ancient sculpture works in Kurdistan. The research also relies on artistic, social, archaeological, and geographical dimensions of the archaeological areas from which the research sample is drawn. It involves examining, recording, and analyzing the characteristics, shapes, signs, and symbols of the research sample's sculptures, as well as the method of classifying their identities and artistic meanings. This is done in order to open new avenues for achieving the original artistic identity of ancient sculptures in Kurdistan.